2019
DOI: 10.1016/j.msea.2018.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Compressive characteristics and low frequency damping of aluminium matrix syntactic foams

Abstract: Al99.5 and AlSi12 matrix syntactic foams were produced by pressure infiltration of Globocer grade ceramic hollow spheres. The produced aluminium matrix syntactic foams (AMSFs) were investigated by compressive tests, dynamic mechanical analysis (DMA), finite element methods (DMA) and elasticity based analytical calculations. The aim of the investigations was (i) to map the compressive properties of the AMSFs, (ii) to determine and compare the effective Young's modulus of the AMSFs determined by compressive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…The volumetric energy absorption capacity, W , of investigated PU foams is defined by Equation (1), and by using variable integration limits, it can be interpreted as the area under the engineering stress-engineering strain curves [57,58]. W=0εσdε …”
Section: Resultsmentioning
confidence: 99%
“…The volumetric energy absorption capacity, W , of investigated PU foams is defined by Equation (1), and by using variable integration limits, it can be interpreted as the area under the engineering stress-engineering strain curves [57,58]. W=0εσdε …”
Section: Resultsmentioning
confidence: 99%
“…Metallic foams, especially Aluminum foams (AF), have recently received attention because of their outstanding physical and chemical properties, including low density, high specific strength, impacting energy absorption, sound absorption, flame resistance and electromagnetic shield effectiveness [1][2][3][4][5][6][7][8]. Due to these aforementioned capabilities, metal foams can be used for many industrial applications such as aerospace, marine, railway, automotive and construction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Metal matrix syntactic foams (MMSFs) are closed-cell porous structures with high stiffness-to-weight ratio. For example, Katona et al reported modulus of elasticity values around 20 GPa for two different types of aluminium foams [49]. Linul et al tested stiffness of aluminium foam panels with stainless steel reinforcement, at extreme temperatures, between −196 °C and 250 °C.…”
Section: Discussionmentioning
confidence: 99%